2019
DOI: 10.29187/jscmt.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength variation of alkali activated fly ash/slag concrete with different NaOH concentrations and sodium silicate to sodium hydroxide ratios

Abstract: Waste disposal becomes a crucial issue for both the environment and the economy. One of the solutions for waste disposal is to utilize waste materials in concrete production. Nowadays, alkali activ ated concrete takes attention since waste materials (fly ash and ground granulated blast furnace slag) are utilized instead of ordinary Portland cement as binder materials. In this study, alkali activated fly ash/slag concrete is produced using 50% F-type fly ash and 50% ground granulated blast furnace slag and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A value of 1.17 was found the best for GPC under ambient curing [ 51 ]. Other tests by Niş [ 64 ] showed that the critical silicate modulus depends on the molarity, in which for 14 M there was a ratio of 1, while for lower molarities the recommended value is 2. This finding supports that obtained previously by Rattanasak and Chindaprasirt [ 65 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
“…A value of 1.17 was found the best for GPC under ambient curing [ 51 ]. Other tests by Niş [ 64 ] showed that the critical silicate modulus depends on the molarity, in which for 14 M there was a ratio of 1, while for lower molarities the recommended value is 2. This finding supports that obtained previously by Rattanasak and Chindaprasirt [ 65 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
“…Nis [ 139 ] investigated geopolymer content using various NaOH concentrations and sodium silicate to sodium hydroxide ratios. The sodium silicate (Na 2 SiO 3 ) and sodium hydroxide (NaOH) solutions were used with four different sodium silicate to sodium hydroxide ratios (1, 1.5, 2, and 2.5) and three different molarities (6 M, 10 M, and 14 M) for alkali activation to evaluate the impact of these parameters on the compressive strength of the alkali-activated fly ash/slag concrete under ambient-curing (AC) and delayed oven-curing (OC) conditions.…”
Section: Injection Moulding Processmentioning
confidence: 99%
“…Based on various studies [ 137 , 138 , 139 , 140 , 141 ], the mechanical characteristics may be affected by the use of different ratios of sodium silicate, sodium hydroxide, and fly ash/alkaline activator. The strongest strength resulted from the fly ash/alkaline activator ratio of 2.0 and the sodium silicate/sodium hydroxide ratio of 2.5, which were used as the ideal ratio for sample preparation.…”
Section: Injection Moulding Processmentioning
confidence: 99%
See 2 more Smart Citations